Impact of Human Resources Practices on Employee Effectiveness in Nigerian Bottling Company, Yola, Adamawa State - Mary Vincent (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the impact of human resources practices on employee effectiveness in Nigerian Bottling Company, Yola, Adamawa State. The study is a survey research design in form of descriptive survey in which data was collected through questionnaire administered to 48 respondents. Data collected was subjected to percentage analysis and hypotheses were tested using regression analysis at 0.05 level of significance. The result revealed that coefficients of the impact of compensation practices on employee effectiveness is statistically significant positive sign (β = 0.469, t = 4.191, p < 0.05). Moreso, coefficients of the impact of career planning practices on employee effectiveness is significant and positive (β = 0.101, t = 0.751, p< 0.05). This means that there is significant positive relationship between employee compensation practices, career planning practices on employee performance in Nigerian Bottling Company, Yola. The study, recommends that the management needs to ensure that enough incentives are given to employee in the organization, i.e. given bonus as form of compensating them for their high performance in the organization. The organization should always have high sense of recognition for employee commitment as form of motivation.